Two successful embryo transfers of mini-donkey embryos in Brazilian Northeastern jennies using an alternative method: Case report - Rodrigues, Lucas T. [UNESP]; Segabinazzi, Lorenzo GTM [UNESP]; Oliveira, Sidnei N [UNESP]; Frasson, Mariana [UNESP]; Papa, Frederico O [UNESP] (Wiley, 2021)
Pregnancy rates after embryo transfer (ET) are disappointing in donkey species. This study aims to report two successful ET of mini-donkey embryos using Brazilian Northeastern jennies as recipients. Eighteen embryo flushes were performed 9 days post-ovulation in two non-pregnant mini-donkeys jennies (11 and 7 cycles per jenny). Eleven embryos (61%, 11/18) were collected and transferred to Brazilian Northeastern jennies 4–6 days post-ovulation by conventional (n = 6) or an alternative (n = 5) technique. The alternative method consisted of inserting a Polansky equine vaginal speculum smeared with lubricant in the vagina of the recipient jenny. The arms of the speculum were extended to allow the visualization of the cervix. Then, using an adapted crafted, elongated, toothed tissue grasping forceps, the external cervical os was held, and the cervix was gently pulled backward, aiming to straight the cervical canal. The ET gun was inserted through the vagina and cervix by visual inspection, and the embryo was released into the uterine lumen. All embryos collected were Grade 1 and classified as Expanded Blastocysts. No jennies become pregnant after conventional ET (0/6), whereas two recipient jennies (40%, 2/5) become pregnant and delivered offspring in the following year after ET using the alternative technique. In conclusion, Brazilian Northeastern jennies can be used as embryo recipients using the alternative method proposed in the present study. However, further investigations are needed to improve the knowledge and results of ET in donkey species.
Keywords: equine; fertility; miniature horse; reproduction